CORPOREIDADE AS SYNONYMOUS OF QUALITY OF LIFE (Fiep Bulletin - online, 2013)
The present research has as objective to verify and to analyze the conception of quality of life of the Professors of Physical Education of the Municipal Net of Education of Campinas-SP, of the region the Northwest. The understanding of the phenomenon quality of life of these professionals was studied, for the speech of the same ones, in view of understanding it, for the methodology of Technique of Elaboration and Analysis of Meaning, elaborated for Moreira; Simões; Porto (2005). The research pointed with respect to a conception of quality of life making a relation of significação to its biological aspect.
Keywords: Physical education; Quality of Vida and Corporeidade